Pengaruh Media Pembelajaran Berbasis AI Assistant terhadap Literasi Sains pada Materi Perubahan Wujud Benda Kelas IV - Marlinda Salwa Talitha Tsany; Ali Ismail; Regina Lichteria Panjaitan (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
Science literacy among Indonesian elementary school students remains relatively low, as reflected in difficulties explaining scientific phenomena, interpreting data, and applying scientific concepts to everyday situations. Artificial Intelligence (AI)-based learning media offer an interactive, student-centered approach to address this issue. This study aimed to examine the effect of AI Assistant-based learning media on the science literacy of fourth-grade students in learning changes in the states of matter. A quantitative approach with a quasi-experimental method and Nonequivalent Control Group Design was employed. The sample consisted of 32 students assigned to an experimental class and a control class. Data were collected using pretest and posttest science literacy assessments and analyzed through N-Gain, Wilcoxon Signed Rank Test, Mann–Whitney U Test, and Cohen's d Effect Size. The results showed a significant difference in science literacy improvement between the two groups (Asymp. Sig. = 0.017, p < 0.05). The experimental class achieved a higher average N-Gain (0.64) than the control class (0.48), while Cohen's d value of 0.9226 indicated a large effect. Therefore, AI Assistant-based learning media effectively improved students' science literacy. These findings suggest that AI Assistant can support the implementation of the Merdeka Curriculum and promote innovative science learning in elementary schools.